Unproductive entrepreneurship - The case of the Polish economy - Julita E. Wasilczuk; Katarzyna Stankiewicz (Gdańsk University of Technology, Faculty of Management and Economics, 2017)
Unproductive entrepreneurship is not a common theme undertaken by researchers. The author defines the basic concepts of unproductive entrepreneurship and explains the role of cultural and economic differences in transition countries, in terms of institutional environment. However the main aim is to identify the nature of unproductive entrepreneurship in Poland. The theory for the research was based on the Baumol work. The research model on the Ajzen TPB. 270 Polish entrepreneurs were surveyed in order to define and describe unproductive entrepreneurship in Poland. The surveyed entrepreneurs present a permissive subjective standard regarding tax evasion when the existence of their enterprise is endangered, however they are also quite indulgent in the case of desire to maximize profits. The entrepreneurs represent more negative behavioural beliefs regarding the effectiveness of tax avoidance than regarding the effectiveness of making arrangements with tender participants or paying bribes.
Keywords: D22; D23; O43; 330; unproductive entrepreneurship; types of unproductivity